Pengembangan Media Puzzle Mata Pelajaran IPAS dengan Materi Penawaran dalam Meningkatkan Kemampuan Kerjasama Antar Siswa pada Kelas V SDN 89 Palembang - Arni, Yusni; Kasta, Loves Yogen Ombi; Asmara, Tria; Eriska, Eriska (CV. PUSDIKRA MITRA JAYA, 2025)
This study aims to develop puzzle media in science learning for fifth grade students of SDN 89 Palembang, with the hope of improving the ability of cooperation between students. By using the Research and Development (R&D) approach and the ADDIE method, this learning media is desaigned to be more interesting and effective. The evaluation results show that the use of puzzle media not only improves student’ understanding of the material presented, but also encourages active participation of stident in the learning process.